Impact of Screen Time on Physical Activity and Eating Habits: A Case Study of Promoting Healthier Lifestyles in a School of Dhaka, Bangladesh - Khondokar Sabera Hamid; Khan Md. Hasanuzzaman (Universal Journal of Educational Research)
This research looks for the effects of screen time on physical activity and eating behavior among primary school children in a school located in Dhaka City. The significance of the research lies in the increasing concerns regarding the effect that screen time has on children's health, alongside the unique opportunity schools have in encouraging healthy behavior, through incorporating physical activity and nutrition education within the students' daily lives. In this study, data was gathered through interviews with 20 parents, 10 teachers, and the head teacher, as well as focus group discussions with 30 students. The teacher interviews focused on the school’s strategies to integrate physical activity and health education into the curriculum. The head teacher’s interview provided insights into the school’s broader health initiatives, while the focus group discussions with students revealed their screen time habits, physical activity preferences, and eating behaviors. The findings indicated the most important position schools can play in fostering a healthier lifestyle. Physical education classes, health promotion programs, and parental involvement positively impact students' levels of physical activity and nutrition. Challenges like small outdoor space at home and busy schedule of the parents hinder the way, whereas the school's initiative seems to be turning the tide toward healthier habits. It concludes with recommendations for schools to continue strengthening their health initiatives and collaborate with parents to reduce screen time, increase physical activity, and promote better nutrition for the well-being of children in urban settings.